2021
DOI: 10.1186/s12912-021-00766-1
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ experiences of the causes of their lack of interest in working in psychiatric wards: a qualitative study

Abstract: Background The shortage of psychiatric nurses is a major healthcare challenge. Lack of interest (LOI) contributes to the shortage of psychiatric nurses. Nonetheless, there are limited studies in this area. The present study was conducted to explore nurses’ experiences of the causes of their LOI in working in psychiatric wards. Methods This qualitative study was conducted in 2016–2019 using the content analysis approach. Participants were 27 nurses … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 30 publications
2
19
0
1
Order By: Relevance
“…This study showed that the SAQ score was not significantly different between psychiatric nurses and domestic norms. Hence, although psychiatric nurses are reluctant to work in psychiatric settings due to stressors associated with working in psychiatric settings, emotional burnout, and negative public attitudes toward psychiatric settings (Rahmani et al, 2021), studies have reported that most nurses choose to work in psychiatric hospitals only when there are no other employment opportunities (Atashzadeh-Shoorideh et al, 2018). For those engaged in psychiatric nursing, it does not affect the overall self-acceptance attitude.…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that the SAQ score was not significantly different between psychiatric nurses and domestic norms. Hence, although psychiatric nurses are reluctant to work in psychiatric settings due to stressors associated with working in psychiatric settings, emotional burnout, and negative public attitudes toward psychiatric settings (Rahmani et al, 2021), studies have reported that most nurses choose to work in psychiatric hospitals only when there are no other employment opportunities (Atashzadeh-Shoorideh et al, 2018). For those engaged in psychiatric nursing, it does not affect the overall self-acceptance attitude.…”
Section: Discussionmentioning
confidence: 99%
“…This kind of stigma may discourage prospective MHPs from entering the profession. For instance, negative attitudes toward psychiatric nurses from the public, colleagues, and family members contributed to nurses’ lack of interest in working in psychiatric settings (Rahmani et al, 2021). As a result, this may decrease the number of trainees choosing psychiatry as a career and exacerbate the shortage of MHPs.…”
Section: Occupational Stigma In Mhpsmentioning
confidence: 99%
“…Psychiatric nurses navigate patient treatment and navigate intricate relationships with patients and their families. Nonetheless, these nurses contend with societal biases (Rahmani et al, 2021), modest remuneration, limited societal status and elevated psychological stress (Greaves et al, 2018). These stressors can engender negative emotions, hinder proactive communication, and curtail emotional perception skills among nurses (Zeb et al, 2021).…”
Section: Introductionmentioning
confidence: 99%